Comparative evaluation of Friesian-Sahiwal and Friesian Hariana halfbreds at different military farms - RAHEJA, K L (The Indian Journal of Animal Sciences, 2013)
Data consisting of first lactation and lifetime performance records of 1 380 Friesian-Sahiwal (FS) and 690 Friesian-Hariana (F:H) halfbreds maintained al 6 milntary dairy farms were analysed. I:S halfbreds yielded 271 kg more milk In first lactation than I.H halfbreds at Agra, whereas FS halfbred produced 175 kg less milk than FH halfbreds at Lucknow. First lactation profit was negative in both genctic groups. FS gave more loss in first lactation than FH halfbreds at Ambala, whercas F.H hallbreds gave more loss at Bareilly and Jhansi. The first calving Interval was longer in FS halfbreds at Barcilly and Meerut. FS has halfbreds completed more lactations than FH halfbreds at Barcilly ,Jhansi and Meerut. F:S had longer herd Me than FH halfbreds at Agra, Barcilly, Jhansi and Meerut. The F:S halfbred. yielded more milk during life lime than FH halfbreds at Agra, Barcilly, Jhdnsi and Meerut FH produced more milk than FS at Lucknow. I:S halfbreds yielded more profit in life than FH halfbrcd< at all farms except Lucknow. The performance of the two genetic groups differed at dffrerent farms.